Critical education analysis of the field ‘child and sciences’ in the new Greek early childhood education curriculum - Μόκιας Αλέξανδρος; Σιάτρας Αναστάσιος; Μιχαλοπούλου Αικατερίνη (Education Sciences, 2023)
The paper aims to analyze the ‘Child and Sciences’ field of the new Greek Early Childhood Education (ECE) curriculum by focusing on learning objectives included in Mathematics, Science and Engineering/Technology units. It has been argued that curriculum reforms in ECE emphasize an academic, cumulative and neutral form of content knowledge that promotes a competitive school environment. Within this qualitative framework, we explore the forms of knowledge produced around ECE by analyzing the learning objectives related to: a) content knowledge, b) nature of knowledge, c) scientific methods, and d) socio-scientific issues. We examine the interaction between abstract academic discourse and the discourse of everyday practices and experiences. Analysis results show that learning objectives are mainly focused on aspects related to abstract academic discourse in all three units (i.e., Mathematics, Science, Engineering/Technology), while the ‘everyday’ discourse appears in many learning objectives of the Engineering/Technology unit. We support the idea that curriculum analysis presented in this paper formulates a critical perspective of the ECE process in order to develop key-competencies for all young children.